2005
DOI: 10.1128/iai.73.4.2147-2156.2005
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein D Is Present in Human Tear Fluid and the Cornea and Inhibits Epithelial Cell Invasion byPseudomonas aeruginosa

Abstract: We have previously shown that human tear fluid protects corneal epithelial cells against Pseudomonas aeruginosa in vitro and in vivo and that protection does not depend upon tear bacteriostatic activity. We sought to identify the responsible tear component(s). The hypothesis tested was that collectins (collagenous calciumdependent lectins) were involved. Reflex tear fluid was collected from healthy human subjects and examined for collectin content by enzyme-linked immunosorbent assay (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 38 publications
5
75
0
Order By: Relevance
“…Error bars are standard errors. pathology, extrapulmonary SP-A has been described in the intestine, 10,44 corneal surface and lacrimal system, 45,46 amniotic and vaginal fluid, 12,47 and recently, in brain tissue. 48 Multiple epitope sites on the protein make detection a challenge, but newer ELISA methods have had greater reproducibility in protein detection.…”
Section: Sp-a and Its Expression In Retinamentioning
confidence: 99%
“…Error bars are standard errors. pathology, extrapulmonary SP-A has been described in the intestine, 10,44 corneal surface and lacrimal system, 45,46 amniotic and vaginal fluid, 12,47 and recently, in brain tissue. 48 Multiple epitope sites on the protein make detection a challenge, but newer ELISA methods have had greater reproducibility in protein detection.…”
Section: Sp-a and Its Expression In Retinamentioning
confidence: 99%
“…Such SP-D-mediated innate immunity is not limited to Klebsiella. A recent study showed that SP-D inhibits the adherence of Pseudomonas aeruginosa to corneal epithelial cells (65).…”
Section: Interaction Of Klebsiella O Antigen Of Lps With C-type Lectinsmentioning
confidence: 99%
“…[8][9][10][11][12] In addition, bathing tear fluid contains mucins, secretory immunoglobulin A (sIgA), and surfactant protein D, all antimicrobial factors that can bind microbes and potentially alter their interactions with corneal epithelial cells. [13][14][15] Epithelial cells also express several antimicrobial peptides, including human β-defensin 2 (hBD-2), cathelicidin LL-37, 11,12,16,17 and cytokeratin 6A. 18 In addition, superficial epithelial cells can internalise bacteria and then desquamate, thereby reducing the infective load.…”
Section: Corneal Barriers Against Infectionmentioning
confidence: 99%